1996
DOI: 10.1111/j.1365-4362.1996.tb01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Alopecia Areata in Northern India

Abstract: Background. Epidemiologic studies of alopecia areata (AA) are available from USA, Japan, and European countries, but there is a paucity of literature on AA from Asian countries, especially from the Indian subcontinent. Methods. In a prospective, hospital‐based study lasting for a decade (1983–1992), the epidemiology of AA was studied, including associated diseases and risk factors for development of severe AA. Simultaneously a similar study was carried out in age‐ and sex‐matched controls. Results. Eight hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
201
11
31

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(283 citation statements)
references
References 13 publications
40
201
11
31
Order By: Relevance
“…Studies from different parts of the world including a previous study from India reported similar findings. 4 Only 13.2% had onset after 40 years of age; Sharma et al had reported 8.8% whereas western literature have reported 19 to 30%. 4,9 In our study an early childhood onset was exclusively noticed in boys though female preponderance was noted in another study from India.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Studies from different parts of the world including a previous study from India reported similar findings. 4 Only 13.2% had onset after 40 years of age; Sharma et al had reported 8.8% whereas western literature have reported 19 to 30%. 4,9 In our study an early childhood onset was exclusively noticed in boys though female preponderance was noted in another study from India.…”
Section: Discussionmentioning
confidence: 89%
“…4 Only 13.2% had onset after 40 years of age; Sharma et al had reported 8.8% whereas western literature have reported 19 to 30%. 4,9 In our study an early childhood onset was exclusively noticed in boys though female preponderance was noted in another study from India. 4 The duration of AA in our study varied from less than 4 weeks to more than 3 years.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations